Desiminasi Produk Teknologi Pengolahan Bawang Merah di Desa Mandatte Kabupaten Enrekang, Sulawesi Selatan - Uca Uca; Wahidah Sanusi; Amal Amal (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Abstract. Shallot is an abundant type of plant in Enrekang Regency. The availability of human resources in active community groups can be fostered. The lack of equipment and technology in making processed shallots that have high selling points and being able to compete with products that already exist in other areas is a major problem. The solutions offered: (1) training and mentoring to process shallots into durable products of high economic value, (2) training and packaging guidance so that they are attractive, (3) Product marketing strategies. The aim to be achieved is to increase the income of partner groups which will lead to an increase in the welfare of the community and local revenue. The specific target to be achieved is long-lasting crispy fried shallots with high economic value, various attractive packaging. The method used is (1) desk study stage; to focus problems and activities to be carried out including conducting intensive discussions with partners. (2) Training and demonstration with simple technology, (3) Program Monitoring and Evaluation, (4) Reflection of program implementation to see all the advantages and disadvantages of the program and its implementation, (5) Strengthening and improving program which is still lacking. The results of the activity showed that the community and business / farmer groups easily absorbed the simple technology in processing fried shallots but the community's interest in developing businesses into household scale industries was still lacking.